DEVELOPMENT OF MATHEMATICS LEARNING VIDEO MEDIA FOR STUDENTS OF CLASS 5 AT 43RD AMPENAN STATE ELEMENTARY SCHOOL - Muhfi, Naila Asya; Karma, I Nyoman; Erfan, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
This research was conducted to produce a valid and practical mathematics learning video media on the topic of data collection and presentation for fifth-grade students at 43rd Ampenan State Elementary School. This study belongs to the Research and Development (R&D) category, utilizing the ADDIE development model (Analysis, Design, Development, Implementation, ansd Evaluation). The research took place at 43rd Ampenan State Elementary School, and the subjects of this study were 20 students in class 5 at 43rd Ampenan State Elementary School. The research object was the mathematics learning video media related to data collection and presentation. The research instruments included questionnaire sheets of material experts and media experts to find out the validity of the mathematics learning video media, student response questionnaires to evaluate its practicality, and documentation. Data analysis in this research used a Likert scale with scores ranging from 1 to 4, which included the analysis of validity and practicality. The results of this study indicate that the developed mathematics learning video media on data collection and presentation achieved a validity percentage of 83.75% based on the criteria of 'valid' from media experts lecturers, 90% with 'very valid' criteria from material experts lecturers, and 87.5% with 'valid' criteria from material experts teachers. The responses of students in small group trials obtained a percentage of 92.50% with 'very practical' criteria, and the responses of students in field trials obtained a percentage of 95.50% with 'very practical' criteria. Therefore, based on the research findings, it can be concluded that the mathematics learning video media on data collection and presentation is highly suitable in terms of validity and practicality for use as a teaching tool in the fifth-grade classroom at 43rd Ampenan State Elementary School.